Evaluating the Effectiveness of Indonesia-Germany G to G Labor Placement Agreements: Case Study of Indonesian Nurses in Germany - Stefani Putri Kinanti; Pramana, Lintang Atha Zahfirah (Legalita, 2024)
The study titled "Evaluating the Effectiveness of Indonesia-Germany G to G Labor Placement Agreements: Case Study of Indonesian Nurses in Germany" employs a normative research methodology to analyze Indonesia's bilateral agreements with Germany concerning Indonesian migrant workers. Utilizing a statutory approach and a comparative analysis, this research draws on secondary data sourced from legal materials, academic journals, and news articles available online. The primary focus is on the legal frameworks governing the placement of Indonesian nurses in Germany, examining how these agreements facilitate or hinder their integration into the German healthcare system. The findings reveal significant challenges, including issues related to language barriers, credential recognition, and cultural adaptation, which impact the effectiveness of these labor placement agreements. This research aims to provide insights into policy improvements that could enhance the outcomes for Indonesian nurses working abroad. Keywords: Indonesia-Germany G to G Labor Placement Agreements, Indonesian Nurses, Migrant Workers Policy